(untitled) (Scientific journal of the Fergana State University, 2026)
This cross-sectional experimental study analyzed 380 third-year medical students from three Uzbek institutions—Fergana Medical Institute of Public Health (FMIOPH), Andijan State Medical Institute, and Bukhara State Medical Institute—to examine how a locally implemented USMLE-aligned program (delivered only at FMIOPH; n=135) relates to clinical competence and student well-being. Blind, unannounced assessments combined a USMLE-subject knowledge test and UWorld-style clinical vignettes; mental and physical health were surveyed concurrently. Compared with non-program peers (n=245), FMIOPH students demonstrated higher mean performance across pathology, physiology, and biostatistics/epidemiology, aligning with the 2025 USMLE content outline’s emphasis on integrated, organ-system reasoning.